A Study about Sales Management Strategies: Adapting Sales Management in a Global Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today's global industry Managers face challenges that are numerous associated with fulfilling customer's expectations as well as requirements. Due to globalization of products plus services customer care is now more complicated. Plentiful info has helped buyers to take appropriate choice and concerned with the way a sales person is able to fix issue and add value to a service or product. Job of intermediaries is essential to achievement in this competitive worldwide market place. As an outcome product sales managers have brand new struggle of answering brand new setting with innovative methods for controlling as well as encouraging the sales force that defines common sales management as looking at the job of sales manager and also concentrating on techniques utilized to handle, lead aas well as inspire employees